Women's knowledge systems and their potential contribution to leadership and socio-political transformation - Mwagiru, Njeri (GSB: Faculty, 2016)
At a theoretical and practical level of inquiry, the research presented in this thesis explores the potential of women's contributions to epistemology and knowledge for enhanced leadership, organisational performance and sustainable processes of socio-political transformation. The research inquiry is informed by a commitment to promote diversity, equity and sustainability, and prompted by the need to investigate women's continued low representation at senior and leadership levels in organisations, and characteristics of persistent gender bias. The main focus of the practical research is the experience of women in senior and leadership positions in organisations. The practical research inquiry focuses on how organisations facilitate or impede women's contributions to knowledge and leadership processes at senior and leadership levels. The objective of the research was to identify organisational facilitators and obstacles that respectively support or constrict women in senior and leadership positions, particularly with reference to the motivations, collegial relations and decision making capacity of women in leadership. A main stipulation of the research theoretical discussion is that current emergence of knowledge economies and societies, in environments of complexity and uncertainty, presents an opportune moment to explore diverse knowledges which may enhance leadership, organisational innovation and performance, as well as sustainable processes of socio-political transformation. In particular, focus is on the potential of women's contributions to knowledge and leadership towards expanded and alternative epistemologies and theoretical frameworks, conceptual models and practical approaches for improved organisational performance and sustainable socio-political transformation. The principal context of interest is Africa, motivated by optimism related to positive patterns of recent economic growth, ongoing processes of democratisation, and a youthful population expanding the region's potential. The discussion references widely however (see References and Bibliography), and may be relevantly applied for a variety of international contexts.